Public Participation in Crowdsourcing Policy Making through Digital Platforms (Universitas Terbuka, 2025)
This study explores public participation in crowdsourced policymaking through digital platforms to enhance inclusiveness, transparency, and accountability in governance. Using a mixed-methods approach, it integrates quantitative survey data with qualitative insights from interviews and focus group discussions. Quantitative analysis examined digital literacy, perceived benefits, ease of use, and participation experiences, while qualitative analysis explored motivations, barriers, and expectations. Results show that respondents generally have high digital literacy and internet access, with positive perceptions of crowdsourcing’s benefits, especially in improving communication with government and promoting transparency. However, trust in the effectiveness of online participation remains moderate due to concerns over data security, inclusivity, and government responsiveness. Although ease of use and willingness to adopt digital platforms are high, participation is still limited by socio-technical and psychological barriers. The study recommends the development of user-friendly and secure platforms with transparent feedback mechanisms, multi-channel accessibility, and strong privacy protections. It emphasizes that successful implementation requires not only technological readiness but also supportive regulations, continuous public outreach, and trust-building efforts. Overall, the research offers both conceptual and practical insights for developing inclusive digital crowdsourcing models suited to the socio-political context of developing countries.